About watches and dials - Nikitin, Валентин; Baizhumanov, Сапархан; Kashagan , Бакыт; Dauletova, Жанна (Рroblems of engineering and professional education, 2023)
Recommendations are given for synchronizing the clock face with the rhythm of human life